Re-examining prophetic traditions: A feminist theological analysis of gender construction in Islamic hadith literature - Afifah, Hana; Anwar, Zaeni; Sukmawardani, Andi Lili; Ilmiawan, Amal Nur; Salamah, Daris; Masruroh, Liana; Fadhlurrahman, Zulfi; Azizi, Adam; Rohmah, Umiatu (Research Journal in Advanced Humanities, 2025)
This article re-examines gender-related prophetic traditions within Islamic hadith literature through an interdisciplinary framework that integrates classical hadith sciences with contemporary feminist theory. Focusing on two frequently debated hadiths, woman’s creation from a rib and the attribution of misfortune to women, the study critically analyzes both their isnad (chains of transmission) and matan (textual content), alongside their historical and socio-cultural contexts. While traditional scholarship has often interpreted these hadiths in ways that reinforce female subordination, this research argues that such readings require re-evaluation in light of both early Islamic corrective voices, particularly that of Sayyidah ʿĀ’ishah, and modern hermeneutical tools. Drawing on Simone de Beauvoir’s existentialist critique of “the Second Sex” and the construction of women as “the Other,” the study reveals how patriarchal interpretations emerged and how they may be deconstructed without undermining the sacred nature of the Prophetic tradition. The findings demonstrate that, when approached through contextual and gender-critical lenses, these hadiths do not legitimize misogyny but instead encourage ethical responsibility and justice in gender relations. By bridging classical Islamic methodologies with feminist theoretical insights, this article contributes to ongoing debates in Islamic studies and gender studies, highlighting the possibility of a more egalitarian and emancipatory understanding of hadith.